Sosialisasi dan Pendampingan Solar PV Rooftop sebagai Sumber Energi Listrik Cadangan di Musholah Baiturrohim Kelurahan Plaju Darat Kecamatan Plaju Kota Palembang: Socialization and Mentoring of Solar PV Rooftop as a Backup Source of Electricity in Baiturrohim Musholah Plaju Darat Village, Plaju District, Palembang City - Roni, Kiagus Ahmad; Sofiah, Sofiah; Afif, Muhammad Faris; Puteri, Delita Mustika; Fadilah, Fadilah (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
Solar photovoltaic (PV) technology, which converts sunlight into electrical energy, is an environmentally friendly applied technology. PV installation on the roof of a building, also known as Rooftop PV, is used not only as a heater but also as an alternative source of electrical energy for a building. Rooftop PV on the Mushola Baiturrohim is used as a backup source of electrical energy when PLN cannot supply voltage. The installed 100 Wp solar photovoltaic system is capable of providing power to a setup consisting of 3 lamps, each with a wattage of 15, and a fan with a diameter of 12 inches, for approximately 2.5 hours. Socialization of the assembly and maintenance of the Rooftop PV system is also carried out for the management of the prayer room and the surrounding community, as a means of transferring renewable energy knowledge that all can utilize.